(untitled) (Indian Journal of Geo-Marine Sciences (IJMS), 2026)
Green tiger shrimp (Penaeus semisulcatus), also known as flower shrimp, is one of Palk Bay’s most economically productive fisheries. Despite the uniqueness of Palk Bay’s fishery, there has been no assessment of the green tiger shrimp’s population parameters in the past 3 decades. The current study aims to understand the population characteristics of P. semisulcatus in Palk Bay. For the study, a total of 14,844 individuals of P. semisulcatus were randomly sampled for length frequency analysis between January 2017 and December 2022. The growth parameters were L∞ = 229.3 mm, k = 1.24 y-1 for males, and L∞ = 270.4 mm, k = 1.14 y-1 for females. Mortality parameters and exploitation ratio estimates recorded were Z = 5.301, M = 2.214, F = 3.087 y-1, E = 0.582 for males, and Z = 5.474, M = 2.002, F = 3.265 y-1, E = 0.634 for females. For both males and females, the Ecurr (current exploitation ratio) was higher than the optimum exploitation ratio (E = 0.5), and the Lm50 (length at maturity) was lower than the LC50 (length at capture). This study generates primary information that provides valuable inputs for developing suitable fishery management plans for the resource from the Palk Bay region, potentially leading to its sustainability certification for trade.